ChemInform Abstract: Enantioselective Decarboxylative Arylation of α‐Amino Acids via the Merger of Photoredox and Nickel Catalysis. Issue 30 (July 2016) - Zuo, Zhiwei; Cong, Huan; Li, Wei; Choi, Junwon; Fu, Gregory C.; MacMillan, David W. C.
Abstract: An enantioselective, decarboxylative C(sp 3 )—C(sp 3 ) cross‐coupling reaction of α‐amino acids with aryl halides by synergistic iridium‐photoredox and nickel catalysis is presented.